Modern interactive platforms as a tool for distance learning in higher education - Cherepok, O.; Volokh, N.; Черепок, Олександр Олексійович; Волох, Наталя Генріхівна (My University, 2021)
The application of new teaching methods in higher education have been especially intensified at the distance learning implementation period during the quarantine. It was necessary to ensure the presentation of the educative material in such way that it was the most accessible and possible for perception, further processing and that feedback was provided.